2015
DOI: 10.1089/ars.2014.5854
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Connection Between Histone Deacetylases, Cell Metabolism, and Cancer

Abstract: High-throughput metabolic studies performed by using more sophisticated technologies applied to the available models of conditional deletion of HDACs in cell lines or in mice will fill the gap in the current understanding and open directions for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 200 publications
(207 reference statements)
0
8
0
Order By: Relevance
“…Conversely, it has also been shown that metabolic intermediates may control HDAC activity in cancer cells 46 . This may represent a cross-talk connecting cell metabolism, transcription, and other HDACs-controlled processes in physiological and pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, it has also been shown that metabolic intermediates may control HDAC activity in cancer cells 46 . This may represent a cross-talk connecting cell metabolism, transcription, and other HDACs-controlled processes in physiological and pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…1,4 HDACs are important epigenetic markers that play a key role in modulating the expression of genes involved in cellular proliferation, apoptosis and differentiation. 5,6 As such, they represent an integrated target for cancer therapy, with the ineffectual metabolism of SCFA in cancer cells hypothesized to lead to an accumulation of acetyl-CoA in the nucleus, where it functions as an HDAC inhibitor. 7 Previous studies have attempted to target and disrupt the altered cellular metabolism in colonic cancer cells via supplementation with SCFA.…”
mentioning
confidence: 99%
“…HDAC class II is further subdivided into class IIa (HDACs 4, 5, 7, and 9) and class IIb (HDACs 6 and 8), with the latter being characterized as having two deacetylase domains [8]. Class IV has only one HDAC member (HDAC11) [11]. The classification and functions of HDACs are shown in Table 1.…”
Section: Classification Of Histone Deacetylasesmentioning
confidence: 99%